Triadimef on, a Systemic Fungicide Against U ncinula N ecator (Oidium) on Wine Grapes: Disease Control, Residues and Effect on Fermentation and Wine Quality - Tromp, A.; Marais, P.G. (South African Journal of Enology and Viticulture, 2017)
The efficacy of the systemic fungicide triadimefon (l-(4-chlorophenoxy)-3,3-dimethyl-l(lH-1,2,4-triazol-1-yl)-2-butanone as a wettable powder spray was evaluated against oldium in field trials. At a high level of infection (86,2% infection), treatment of the grapes with vine sulphur was inadequate (65% infection), while the triadimefon treatment controlled the disease excellently (10,5% infection). Residues recovered from grapes were low, in the order of 0,245 mg/kg on grapes harvested immediately after the final application of the fungicide. Addition of 200 mg triadimefon (active ingredient)/ f, to grape juice had no significant effect on either onset or rate of fermentation. Fermentation of must from triadimefon-treated grapes was also similar to that of must from untreated grapes, and no effect on wine quality could be observed.